Amplatzer occluders for refractory esophago-respiratory fistulas: a case series - Belle, Arthur; Lorut, Christine; Lefebvre, Aurélie; Ali, Einas Abou; Hallit, Rachel; Leblanc, Sarah; Bordacahar, Benoit; Coriat, Romain; Roche, Nicolas; Chaussade, Stanislas; Barret, Maximilien (Endoscopy International Open, 2021)
Background and study aims Endoscopic management of esophagorespiratory fistulas (ERF) is challenging and currently available options (stents, double pigtail, endoscopic vacuum therapy) are not very effective. We report the feasibility and efficacy of endoscopic placement of Amplatzer cardiovascular occluders for this indication.Patients and methods This was a single-center, prospective study (June 2019 to September 2020) of all patients with non-malignant ERF persistent after conventional management with esophageal and/or tracheal stents. The primary outcome was the technical feasibility of Amplatzer placement. Secondary outcomes were clinical success defined by effective ERF occlusion and resolution of respiratory symptoms allowing oral food intake.Results Endoscopic placement of Amplatzer occluders was feasible in 83 % of patients (5/6), with a 50 % (3/6) clinical success rate at 9 months. The mortality rate was 33 % (2/6).Conclusions An Amplatzer cardiac or vascular occluder is a feasible and safe treatment option for refractory ERF, with a 50 % short-term clinical success.